Knowledge of women and men about human papillomavirus infection, HPV-related diseases and the available vaccine - Katarzyna Dobko; Gabriela Frącz; Agata Glac; Klaudia Kuliga; Kinga Musz; Natalia Sejnowska; Agnieszka Socha; Agata Surowiec; Kinga Śnieżek; Anna Zając (Kazimierz Wielki University, 2023)
Introduction: Worldwide, there are over 660 million men and women who are HPV carriers. This virus is responsible for cancer, i.e. cancer of the anal canal, head and neck region, penis and the most common - cervical cancer, whose early stages are completely curable, and in stage IV, the survival rate does not exceed 10%. That is why prevention is so important and vaccinations for both sexes. Aim: The aim of the study was to check the awareness of society, both women and men and men, on the HPV virus - the way it spreads, the diseases it causes and the possibilities of preventing infection, as of the date of entry into force in Poland of the program of free preventive vaccinations for girls and boys aged 12 and 13. Material and methods: The study was conducted in the form of an anonymous online survey containing 21 questions. It was attended by 396 adults. Results: 80% of the population is unaware of how common HPV infection is. 33% of men believe that it occurs 8 times less often than it actually does, and that having an infection protects against another infection. Only 1/5 of women are aware of the risks. Only 15.15% of the respondents know the correlation between cervical cancer and the presence of the virus. 25% of women are not aware of free cytology. Only half of the respondents know about the free HPV vaccination program. 1/3 of people think that only girls should be vaccinated. Conclusions: Public awareness of HPV is insufficient. Men showed greater knowledge than women, and in general people with offspring had the lowest knowledge. This shows that the information campaign related to preventive vaccinations should be carried out on a much larger scale, as they are the most effective method of protecting both women and men.